The role of adverse events after naprapathic manual therapy as a prognostic factor - Tabell, Vesa (2015)
Vesa Tabell (2015). The role of adverse events after Naprapathic Manual Therapy as prognostic factor. Terveystieteiden laitos, Jyväskylän yliopisto, Liikuntalääketieteen pro gradu, 38 sivua.